Determinants of COVID-19 Vaccination Status and Vaccine Hesitancy in the Centre-Est Region of Burkina Faso: A Population-Based Cross-Sectional Study - Kadari Cissé; Eric Ismaël Zoungrana; Abdou Azaque Zouré; Tani Sagna; Guibrine Tao; Sylvie Zida; Danielle Belemsaga; Fatou Sissoko; Désiré Lucien Dahourou; Henri Gautier Ouédraogo (Advances in Public Health)
Conclusion: Our study revealed a lower COVID-19 vaccine rate and a higher vaccine hesitancy rate in the Centre-Est Region of Burkina Faso. Improving communication about COVID-19 preventive measures might increase adherence to COVID-19 vaccination.